Resprouters, assisted by somatic mutations, are as genetically diverse as nonsprouters in the world's fire-prone ecosystems - Fowler, W.; Deng, X.; Lamont, Byron; He, Tianhua (Elsevier, 2018)
In fire-prone environments worldwide, resprouters mostly regenerate vegetatively after fire, whereas non (re)sprouters are killed by fire and rely entirely on stored seeds (soil or canopy storage) for regeneration. This dichotomy in post-fire regeneration strategies is a key mechanism for controlling the reproductive characteristics, demography, and population genetic structure of plant species in fire-prone ecosystems. Nonsprouters are considered to have higher within-population genetic variation than resprouters due to greater opportunities for recombination via their much greater seed production and frequent generation turnover. Empirical studies that explore this hypothesis are rare and the results are mixed. We collated published studies reporting genetic diversity measures of plant species in fire-prone ecosystems of four Mediterranean-climate regions. Ninety-two species were identified with unambiguous information on postfire regeneration type and with adequate sample sizes. We found no significant differences in population genetic diversity and structure between resprouters and nonresprouters across diversity parameters and genetic marker types, taxon groups or geographic regions. We conclude that resprouters are at least as genetically diverse as nonsprouters. We tested the hypothesis that accumulation of somatic mutations is a possible mechanism for maintaining genetic diversity among resprouters, by screening for microsatellite DNA mutations in the resprouter, Banksia attenuata. Genotyping of leaf material collected from disparate parts of individual plants demonstrated the existence of 2–5 somatic mutations among eleven microsatellite loci. The buildup of somatic mutations in meristematic buds during a resprouter's long lifespan and the considerable potential for interpopulation gene dispersal among resprouters may be key factors that enable their genetic diversity to keep pace with that of nonsprouters. Thus, resprouters and nonsprouters are equally capable of responding to natural selection, and therefore possess a similar potential to adapt to changing environmental conditions.